Upaya Meningkatkan Kemampuan Berpikir Kritis Siswa Melalui Model Pembelajaran Deep Dialogue/ Critical Thinking (DD/CT) Pada Mata Pelajaran Fiqih Kelas VIII MTS N 1 Langkat - Siti Darmawani, Usmaidar, Rani Febriyanni (Pusdikra Publishing, 2023)
This study aims to determine the critical thinking skills of students in Fiqh learning after the application of the Deep Dialogue / Critical Thinking (DD / CT) Learning Model in class VIII MTs N 1 Langkat. This research is included in class action research (Action Research). This study uses a type of collaborative model, namely researchers with Fiqh study teachers in class VIII MTs N 1 Langkat. The subjects in Class Action Research VIII are students of class VIII MTs N 1 Langkat with a total of 32 students. the instruments in this researcher are observation sheets and tests in accordance with the research procedures by observing cycle I and cycle II. The application of the Deep Dialogue/Critical Thinking learning method can be implemented well through two cycles. This can be seen through the activities of students in cycle I and cycle II have increased. The results of observations of student activity in learning which initially in cycle I only reached a score of 67.5% then increased by 17.5% to 85% in cycle II. There is a difference in the critical thinking skills of students in class VIII MTs N 1 Langkat between before and after the implementation of class action research using the Deep Dialogue / Critical Thinking learning method, this is known from the completeness of learning in class VIII MTs N 1 Langkat in the pre-cycle is 66.71% while in cycle I reached 72.96% and in cycle II amounted to 80.93% . After the application of the Deep Dialogue / Critical Thinking learning method, students' critical thinking skills have increased, this can be seen from the results of the pre-cycle critical thinking skills test which only reached an average score of 66.71 (less) and increased in cycle I to 72.96% (sufficient) and in cycle II increased again to 80.93% (good). The increase in critical thinking skills can also be seen in the increase in the percentage of student completeness, namely in the pre-cycle only 40.62% while in cycle I it reached 65.62% and in cycle II it was 84.37%. In addition, from the test results it is known that in cycle I and cycle II the Sig (2- Tailed) value is 0.000. <0.05, it can be concluded that there is a significant difference between the pre-test and post-test learning outcomes. Therefore, it is concluded that the use of the Deep Dialogue/Critical Thinking method can improve students' critical thinking skills.